Dados os números complexos u = 1 + i e v = 1 - i, calcule u (elevado a 52) . v (elavado a - 51)
Soluções para a tarefa
Respondido por
5
Resposta:
1 - i
Explicação passo-a-passo:
Temos que:
u^52. v^(-51) =
(1 + i)^52. (1 - i)^(-51) =
(1 + i)^52. (1 - i)^(-52+1) =
(1 + i)^52. (1 - i)^(-52). (1 - i) =
(1 + i)^52. [1/(1 - i)]^52. (1 - i) =
[(1 + i)/(1 - i)]^52. (1 - i) =
[(1 + i)/(1 - i) . (1 - i)/(1 - i)]^52. (1 - i) =
[ (1 + i).(1 - i) / (1 - i)^2 ]^52. (1 - i) =
[ (1^2 - i^2) / (1 - i)^2 ]^52. (1 - i) =
[ (1 - (-1)) / (1 - i)^2 ]^52. (1 - i) =
[ 2 / (1 - i)^2 ]^52. (1 - i) =
[ 2 / (1^2 - 2.1.i + i^2) ]^52. (1 - i) =
[ 2 / (1 - 2i -1) ]^52. (1 - i) =
[2/(-2i)]^52. (1 - i) =
(-1/i)^52. (1 - i) =
1 / i^52. (1 - i) =
(1 - i) / (i^2)^26 =
(1 - i) / (-1)^26 =
(1 - i) / 1 =
1 - i
Blz?
Abs :)
Perguntas interessantes